Leigh Syndrome: Cranial MRI and MR Spectroscopy Findings - Aydın, Hasan; Kızılgöz, Volkan; Hekimoğlu, Baki (Fırat University, 2011)
A 10 years old girl, was admitted to the intensive care unit with seizure, myotonic-clonic jerks in her hands, vomiting, respiratory failure and mild metabolic acidosis. Brain Magnetic resonance imaging (MRI) and proton MR spectroscopy(MRS) were performed.The MRI findings presented symmetric basal ganglia, brain stem, left thalamus and subthalamic nuclei involvement. MRS obtained from the basal ganglia and thalamus lesions, showed increased lactate and choline peak, decreased NAA\Crea and NAA\Cho ratios. In the CSF, there was also increased lactate. These imaging findings, clinical course and the laboratory data were used for the diagnosis of Juvenile form of Leigh syndrome. Muscle biopsy wasn't needed for the diagnosis.

On yaşında kız çocuğu acil ünitesine; nöbet, ellerinde myotonik-klonik kasılmalar, kusma, solunum kaybı ve hafif metabolik asidoz bulguları ile başvurdu. Beyin Manyetik Rezonans Görüntüleme (MRG) ve proton-MR Spektroskopi yapıldı. MRG bulguları; Simetrik bazal ganglion, beyin sapı, sol talamus ve subtalamik çekirdek tutulumu içermekteydi. Bazal ganglion ve talamus lezyonlarından alınan MR Spektroskopi de; artmış laktat ve kolin pikleri, azalmış NAA\Krea and NAA\Kol oranlarını gösterdi. Beyin omurilik sıvısında da artmış aktat mevcuttu. Görüntüleme bulguları ile birlikte klinik süreç ve laboratuar verileride Leigh sendromu genç erişkin tip tanısını desteklediğinden, teşhis için kas biyopsisine gerek duyulmadı.
Leigh Sendromu: Beyin MRG ve MR Spektroskopi Bulguları